Hybrid operating room for the multidisciplinary treatment of a juvenile nasoangiofibroma at the “Dr. Eduardo Liceaga” general hospital of Mexico: case report and literature review - Cabrera, Maria Fernanda; Lule Gonzalez, Maria Corina; Molina Carrasco, Fatima del Rosario; Jerez Robalino, James Phillipe; Naranjo, Julia Rodriguez; Hernández, Jorge Francisco Moises; Farrera, Gabriel Fernando Paredes (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Nasoangiofibroma or juvenile nasopharyngeal angiofibroma is a highly vascularized benign neoplasm, which mainly affects men between the first and second decade of life. The incidence of this type of lesion is extremely rare and occurs in a 0.05 to 0.5% of all head and neck neoplasm, in which surgical treatment is considered the best treatment option. Treatment of this pathology in a hybrid operating room is considered a novel tool, to carry out an effective multidisciplinary intervention, granting better control of the procedure and hemostasis. The purpose of this publication is to describe the advantages of performing surgery in a hybrid operating room, as well as to conduct a literature review on this condition. Two cases are reported, a 14 and 16-years old male, both with a probable diagnosis of juvenile nasoangiofibroma. The surgical treatment was carried out in the hybrid operating room of the General Hospital of Mexico “Dr. Eduardo Liceaga” by the otorhinolaryngology and the oral and maxillofacial surgery department after embolization by the interventional radiology team.